Colonization history and clonal richness of asexual Daphnia in periglacial habitats of contrasting age in West Greenland. (9th May 2016) - Haileselasie, Tsegazeabe H.; Mergeay, Joachim; Weider, Lawrence J.; Jeppesen, Erik; De Meester, Luc
Summary: Due to climate change, Arctic ice sheets are retreating. This leads to the formation of numerous new periglacial ponds and lakes, which are being colonized by planktonic organisms such as the water flea Daphnia . This system provides unique opportunities to test genotype colonization dynamics and the genetic assemblage of populations. Here, we studied clonal richness of the Daphnia pulex species complex in novel periglacial habitats created by glacial retreat in the Jakobshavn Isbræ area of western Greenland. Along a 10 km transect, we surveyed 73 periglacial habitats out of which 61 were colonized by Daphnia pulex . Hence, for our analysis, we used 21 ponds and 40 lakes in two clusters of habitats differing in age (estimated <50 years vs. >150 years). We tested the expectation that genetic diversity would be low in recently formed (i.e. young), small habitats, but would increase with increasing age and size. We identified a total of 42 genetically distinct clones belonging to two obligately asexual species of the D. pulex species complex: D. middendorffiana and the much more abundant D. pulicaria . While regional clonal richness was high, most clones were rare: 16 clones were restricted to a single habitat and the five most widespread clones accounted for 68% of all individuals sampled. On average, 3·2 clones (range: 1–12) coexisted in a given pond or lake. There was no relationship between clonal richness and habitat size when we controlled for habitat age. Whereas clonal richness was statistically higher in the cluster of older habitats when compared with the cluster of younger ponds and lakes, most young habitats were colonized by multiple genotypes. Our data suggest that newly formed (periglacial) ponds and lakes are colonized within decades by multiple genotypes via multiple colonization events, even in the smallest of our study systems (4 m 2 ). Abstract : The authors analysed clonal richness and diversity in populations of the water flea Daphnia inhabiting periglacial ponds and lakes created by glacial retreat in western Greenland and show that, irrespective of habitat size, habitats are within decades colonized by multiple clones, implying high dispersal rates in these novel landscapes.